1997
DOI: 10.1074/jbc.272.34.21096
|View full text |Cite
|
Sign up to set email alerts
|

Novel Inhibitors of Cytokine-induced IκBα Phosphorylation and Endothelial Cell Adhesion Molecule Expression Show Anti-inflammatory Effects in Vivo

Abstract: We have identified two compounds that inhibit the expression of endothelial-leukocyte adhesion molecules intercellular adhesion molecule-1, vascular cell adhesion molecule-1, and E-selectin. These compounds act by inhibiting tumor necrosis factor-␣-induced phosphorylation of IB-␣, resulting in decreased nuclear factor-B and decreased expression of adhesion molecules. The effects on both IB-␣ phosphorylation and surface expression of E-selectin were irreversible and occurred at an IC 50 of approximately 10 M. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
754
4
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 992 publications
(796 citation statements)
references
References 73 publications
36
754
4
2
Order By: Relevance
“…Because activation of the iNOS promoter by C. crepidioides required the activation of NF-κB, we blocked NF-κB activation with Bay 11-7082, an inhibitor of IκBα phosphorylation [24] or LLnL, a proteasome inhibitor [25]. Bay 11-7082 and LLnL reduced C. crepidioides -induced iNOS promoter activity (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because activation of the iNOS promoter by C. crepidioides required the activation of NF-κB, we blocked NF-κB activation with Bay 11-7082, an inhibitor of IκBα phosphorylation [24] or LLnL, a proteasome inhibitor [25]. Bay 11-7082 and LLnL reduced C. crepidioides -induced iNOS promoter activity (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Bay 11-7082 and LLnL are relatively specific inhibitors of NF-κB activation [24,25]. Both agents blocked the promoter activity of iNOS, the expression of iNOS mRNA, and the production of nitrite, indicating the likely involvement of NF-κB in the induction of not just iNOS-driven reporter constructs but also the iNOS gene itself in C. crepidioides -treated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the combination of bile and acid (pH ≤4.0) constitutively activates NF‐κB, up‐regulating the expression of cancer‐related genes and deregulating the expression of oncogenic miRNA markers, such as “oncomirs” miR‐21, miR‐192, miR‐155 and “tumour suppressors” miR‐34a, miR‐375 and miR‐451a, in pre‐malignant lesions of murine laryngopharyngeal mucosa 9, 10. Here, we describe an in vitro model exploring repetitive exposures of normal human hypopharyngeal cells to acidic bile, with and without BAY 11‐7082, a pharmacologic inhibitor of NF‐κB 11. We hypothesize that NF‐κB inhibitor is capable of preventing the acidic bile‐induced up‐regulation of “oncomirs” miR‐21, miR‐155 and miR‐192 and down‐regulation of “tumour suppressor” miR‐34a, miR‐375 and miR‐451a, previously associated with laryngopharyngeal cancer,12, 13, 14, 15, 16, 17 providing insight into interactions of transcriptionally active NF‐κB with cancer‐related miRNA markers.…”
Section: Introductionmentioning
confidence: 99%
“…BAY 11‐7082 was selected as a reliable inhibitor of NF‐κB pathway that has been widely used in many studies exploring the effect of NF‐κB 11, 24, 25. It has been suggested that BAY 11‐7082 offers the most rapid and potent antitumour effect among other NF‐κB inhibitors 24 and can possibly be used as a sensitizer of anticancer therapy,26, 27 increasing the intrinsic susceptibility of cancer cells to chemotherapeutic agents 28…”
Section: Introductionmentioning
confidence: 99%
“…1B). DC pretreated with BAY11-7082, an inhibitor of IkBa processing [18], and incubated with VLP or LPS also showed a decreased nuclear expression of p65 compared with control DC. By flow cytometry and by Western blotting, BAY11-7082 was also found to have an inhibitory effect on CXCR4 expression in DC stimulated by VLP or LPS compared with DC activated by VLP or LPS alone ( Fig.…”
Section: Direct Effects Of Hpv Particles On DC Traffickingmentioning
confidence: 96%